2004
DOI: 10.1002/j.2168-9830.2004.tb00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying and Removing a Calculus Prerequisite as a Bottleneck in Clemson's General Engineering Curriculum

Abstract: A review of prerequisites often reveals that reasons for requiring a prerequisite may no longer prevail due to curriculum or course changes. Based on a study of a curriculum bottleneck unrelated to required mastery, the prerequisite structure in Clemson University's General Engineering curriculum (the common firstyear curriculum for all engineering students) was changed so that Calculus I could be taken in the second semester. Student record analysis shows both the magnitude of the bottleneck prior to the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 3 publications
2
44
0
Order By: Relevance
“…Budny et al concluded that an algebra placement exam should be used to identify students for placement in a remediation course. Seeming to confirm these results is a study by Ohland, Yuhasz, and Sill [17] that showed an improvement in engineering retention by recognizing that many students were not ready to take calculus in their first semester.…”
Section: Relationship Between Engineering Retention and First Mathemasupporting
confidence: 67%
“…Budny et al concluded that an algebra placement exam should be used to identify students for placement in a remediation course. Seeming to confirm these results is a study by Ohland, Yuhasz, and Sill [17] that showed an improvement in engineering retention by recognizing that many students were not ready to take calculus in their first semester.…”
Section: Relationship Between Engineering Retention and First Mathemasupporting
confidence: 67%
“…Previous studies have already shown that grades students earn in their first mathematics course influences their retention in engineering 10,11 . How do the grades students earn influence their progress through the mathematics sequence?…”
Section: How Much Difference Does the Grade In The First Mathematics mentioning
confidence: 97%
“…For instance, [Ohland et al 2004] found that removing a gateway course for their engineering major improved graduation rates for the major as a whole, suggesting that the course was not a true prerequisite. Every curriculum is subject to time constraints, and knowing which units can be safely omitted if necessary is important.…”
Section: Discussionmentioning
confidence: 99%